Exploring pedagogical approaches in crown preparation: a randomized controlled trial comparing the efficacy of instructional videos and live demonstrations - Maria Shakoor Abbasi; Ayesha Anis; Sarah Billoo; Sara Altamash; Ambreen Afzal Ehsan; Syed Ahmed Omer; Duygu Ilhan; Zarak Khan; Naseer Ahmed; Gotam Das; Seyed Ali Mosaddad (BMC Medical Education)
Abstract Background This study aimed to compare the efficacy of instructional videos and live demonstrations in crown preparation training for preclinical dental students. Methods A randomized controlled trial was conducted over 12 months with 96 final-year Bachelor of Dental Surgery (BDS) students. Participants were randomly allocated into three groups: Group A (instructional video), Group B (live demonstrations), and Group C (hybrid approach). Each group underwent training in porcelain-fused-to-metal tooth preparation through their respective methods. Performance was assessed using a standardized scoring chart, while satisfaction and perceptions were evaluated using a 5-point Likert scale. Data were analyzed using Chi-square and paired t-tests, with statistical significance set at p < 0.05. Results The group comparisons revealed significant differences in perceptions between Group A and Group B regarding stress levels during crown preparation (p = 0.013) and the adequacy of preclinical training (p = 0.034), with Group B showing higher satisfaction. However, no significant differences were found between Groups A and C or between Groups B and C (p > 0.05). Exercise scores across all groups showed no significant variation (p > 0.05), indicating comparable performance. Knowledge assessment revealed that while a majority of students correctly identified key concepts such as finish line depth, bur choices, and cusp reduction, 10–16% of students held misconceptions in areas like margin design and reduction ranges. Conclusion This study demonstrates that instructional videos, live demonstrations, and a hybrid approach are all effective methods for teaching crown preparation skills to preclinical dental students. The slight advantage of the hybrid approach suggests that combining different teaching methods may provide the most comprehensive learning experience. Future studies should explore the long-term impact of these methods on clinical performance. Trial registration The study was registered at clinicaltrials.gov, identifier NCT06426095.